Groundwater chemical anomalies connected with the Kamchatka earthquake (M=7.1) on March 1992 - P. F. Biagi; P. F. Biagi; L. Castellana; A. Minafra; G. Maggipinto; T. Maggipinto; A. Ermini; O. Molchanov; Y. M. Khatkevich; E. I. Gordeev (Natural Hazards and Earth System Sciences, 2006)
The energy released by the earthquakes occurred in the seismogenetic area of the southern Kamchatka (Russia) from January 1977 to December 2004, reveals an increase in the peak energy in the period 1992–1999. This increase is related to the occurrence of seven earthquakes with magnitude ranging from 6.9 to 7.7; the first of these earthquakes happened on 2 March 1992 with M=7.1. For many years, hydro-geochemical data have been collected with a mean sampling rate of three days, in the form of the most common ions and gases in the water of deep wells and natural springs of a network operating in the south area of the Kamchatka, where the capital city Petropavlovsk is located. The collected data were analysed and differences in the trend and in the spectral content of some hydro-geochemical parameters at the springs were pointed out before and after the occurrence of the March 1992 earthquake, indicating clear post-seismic effects. Then an evident increase in the Carbon Dioxide and in the Hydrogen content appeared practically at each measurement site during the two-four years preceding the earthquake, so that long term precursors can be claimed. Finally, an anomalous decrease in the Carbon Dioxide content at the springs was revealed two/three months prior the earthquake, as a middle term precursor. The earthquake on March 1992 was the event nearest (90–120 km) to the measurement sites that happened in last thirty years.